A simplified approach to optimize wave attenuation for floating energy islands: the role of flat plates (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Recent advancements in offshore energy technologies have positioned floating offshore energy islands as cost-effective solutions for large-scale marine energy production [1]. The Mediterranean Sea, abundant in natural resources such as waves, wind, and solar irradiation, has been identified as an ideal location for the innovative Floating Energy Archipelago, a concept recently proposed by the National Research Council of Italy. A key challenge in realizing this vision lies in creating a sheltered marine area with reduced wave heights, enabling the safe deployment of floating renewable energy systems, such as solar islands [2].To address this challenge, the hydrodynamic performances of a box-type floating breakwater augmented with flat plates are evaluated in this study. The flat plates, arranged symmetrically and asymmetrically, are designed to improve wave attenuation, with their effectiveness assessed through key performance metrics such as transmission, reflection, and dissipation coefficients [3]. Additionally, the dynamic response of the structure under various sea states is analyzed, offering critical insights into its feasibility for integration with a Power Take-Off system. This dual analysis is crucial: wave attenuation performance determines the capability of the breakwater in protecting the energy archipelago, while global wave-induced motion inform future PTO system design and implementation.This study develops a simplified numerical model based on Morison-type equations to provide an efficient decision-support framework for early-stage design and optimization [4] . To account for viscous effects, the drag coefficient is determined through both experimental testing and high-fidelity Computational Fluid Dynamics simulations. This coefficient is subsequently incorporated into the simplified model to ensure an accurate representation of fluid-structure interactions, with a particular focus on assessing the impact of the flat plates.Preliminary results indicate that the integration of flat plates significantly improves the hydrodynamic performance of the box-type floating breakwater, reducing wave transmission and contributing to the creation of a sheltered area, while enhancing stability under various conditions. The ability to adapt the configuration of the flat plates - whether in terms of symmety and geometry - offers further flexibility to optimize performance based on site-specific requirements.This research highlights the ability of flat plates to enhance wave attenuation in marine infrastructure while supporting the development of hybrid systems with energy generation capabilities. The findings contribute to scalable and cost-effective solutions for the Floating Energy Archipelago, reinforcing its role as a key driver of blue energy transition.